Screening Relevance of Sessile Serrated Polyps - Charles J. Kahi (Clinical Endoscopy, 2019)
Conventional adenomas have historically been considered to be the only screening-relevant colorectal cancer (CRC) precursor lesion. The prevailing paradigm was that most CRCs arise along the chromosomal instability pathway, where adenomas accumulate incremental genetic alterations over time, leading eventually to malignancy. However, it is now recognized that this “conventional” pathway accounts for only about two-thirds of CRCs. The serrated pathway is responsible for most of the remainder, and is a disproportionate contributor to postcolonoscopy CRC. Hallmarks of the serrated pathway are mutations in the BRAF gene, high levels of methylation of promoter CpG islands, and the sessile serrated polyp (SSP). Accumulating evidence shows that SSPs can be considered adenoma-equivalent from the standpoint of CRC screening. SSPs have a higher prevalence than previously thought, and appear to have a relatively long dwell time similar to that of conventional adenomas. In addition, SSPs, whether sporadic or as part of the serrated polyposis syndrome, are associated with increased risk of synchronous and metachronous neoplasia. These features collectively support that SSPs are highly relevant to CRC prevention.